Impact of educational levels on survival rate: A cohort study of 2007 living donor liver transplant recipients at a single large center. Issue 5 (February 2019) - Cho, Seong-Sik; Ju, Young-Su; Park, Hanwool; Kim, Young-Kug; Hwang, Shin; Choi, Seong-Soo
Abstract : Abstract: Among living donor liver transplantation recipients, the impact of educational levels on survival has rarely explored. Thus, the purpose of study is to analyze the survival rate differences across educational levels among recipients who underwent living donor liver transplantation. We retrospectively analyzed 2007 adult recipients who underwent living donor liver transplantation in a single large center. The educational level was divided into three categories: middle school or lower, high school, and college or higher. The primary outcome was all-cause mortality after living donor liver transplantation. Stratified log-rank test and Cox proportional hazard model were employed for statistical analysis. The incidence rates of all-cause mortality were 23.85, 20.19, and 18.75 per 1000 person-year in recipients with middle school or lower, high school, and college or higher education groups, respectively. However, the gender-stratified log-rank test has not shown a statistically significant difference ( P = .3107). In the unadjusted model, hazard ratio (HR) was 1.02 [95% confidence interval (CI) = 0.79–1.33] in high school and 1.23 (95% CI = 0.93–1.64) and in middle school or lower educational level, respectively; In the full adjusted model, the HR of high school was 0.98 (95% CI = 0.75–1.28) and the HR of middle school or lower was 1.01 (95% CI = 0.74–1.37). Although study population of this study is large, we could not find significant survival rate differences by the levels of education. Social selection and high compliance rate might contribute to this result.